2014
DOI: 10.1890/es13-00375.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity in a nutshell: testing for small‐scale effects on trap nesting wild bees and wasps

Abstract: Abstract. Declining plant species richness in agro-ecosystems and thus reduced habitat quality can have cascading effects on ecosystem functioning, leading to reduced pollination and biological control. Here we test if plant diversity can affect arthropod diversity and abundance on a very small scale, manipulating plant species richness (2, 6, 12 and 20 sown species) in small adjacent subplots (6 3 9 m) in 10 wildflower strips in an agricultural landscape. We simultaneously analyzed the effect of plant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 45 publications
3
37
1
Order By: Relevance
“…Usually, the diversity and abundance of trap‐nesting bees and wasps is positively related to the diversity and cover of flowering plants (e.g., Ebeling, Klein, Weisser, & Tscharntke, Tscharntke et al., ) because the imagines visit flowers to consume nectar (bees and wasps) and collect pollen (bees) for brood‐cell provisioning. These findings also support general biodiversity‐ecosystem functioning theory (Cardinale et al., ) and the emerging hypothesis that bottom‐up effects of plant diversity on higher trophic levels already occur at small spatial scales (Albrecht et al., ; Ebeling et al., ; Fabian et al., ). Differing flower availability also explains why bees usually numerically dominate trap‐nesting communities in open landscapes (e.g., Osorio et al., ; Steckel et al., ), while in closed forests, wasps are more abundant (e.g., Staab et al., ; Stangler, Hanson, & Steffan‐Dewenter, ).…”
Section: Discussion and Summary Of Literaturesupporting
confidence: 82%
See 1 more Smart Citation
“…Usually, the diversity and abundance of trap‐nesting bees and wasps is positively related to the diversity and cover of flowering plants (e.g., Ebeling, Klein, Weisser, & Tscharntke, Tscharntke et al., ) because the imagines visit flowers to consume nectar (bees and wasps) and collect pollen (bees) for brood‐cell provisioning. These findings also support general biodiversity‐ecosystem functioning theory (Cardinale et al., ) and the emerging hypothesis that bottom‐up effects of plant diversity on higher trophic levels already occur at small spatial scales (Albrecht et al., ; Ebeling et al., ; Fabian et al., ). Differing flower availability also explains why bees usually numerically dominate trap‐nesting communities in open landscapes (e.g., Osorio et al., ; Steckel et al., ), while in closed forests, wasps are more abundant (e.g., Staab et al., ; Stangler, Hanson, & Steffan‐Dewenter, ).…”
Section: Discussion and Summary Of Literaturesupporting
confidence: 82%
“…These findings also support general biodiversity-ecosystem functioning theory (Cardinale et al, 2006) and the emerging hypothesis that bottom-up effects of plant diversity on higher trophic levels already occur at small spatial scales (Albrecht et al, 2007;Ebeling et al, 2012;Fabian et al, 2014 Tscharntke et al, 2012). For example, the proximity to woody habitats (e.g., forest edges, hedgerows) is often a predictor for trap-nesting bee and wasp abundance (e.g., Fabian et al, 2013;Holzschuh, Steffan-Dewenter, & Tscharntke, 2009), as those habitats provide natural nesting spaces (e.g., in deadwood or hollow twigs).…”
Section: Landscape and Community Ecologysupporting
confidence: 79%
“…The positive relationship between host and natural enemy abundance has been shown in several studies, which distinctly show that with higher resource availability (hosts), the next trophic level (natural enemies) also increases (e.g. Holzschuh et al ., ; Ebeling et al ., ; Fabian et al ., ). A direct effect of a more complex landscape in agricultural areas on natural enemy populations was observed in the majority of studies included in the review by Bianchi et al .…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that sown wildflower strips provide ample resources for this wasp species allowing for efficient nest building in the proximity of these AES elements. Due to their plant species richness and abundance, sown wildflower strips will not only boost caterpillar‐hunting wasps via energetically rich nectar (Fabian et al ., ), but also via abundant prey. Even though caterpillar prey in nests of A. nigricornis consisted exclusively of microlepidoptera, it seems likely that, similar to macrolepidoptera (Aviron et al ., ; Haaland & Bersier, ; van Halder et al ., ), this group of small butterflies benefits from the diversity and quantity of plants in the wildflower strips.…”
Section: Discussionmentioning
confidence: 99%
“…Because complementary work in our study area revealed similar abundances of P. impressa in arable land and wildflower strips (Mader et al ., ), the negative effect of proximity to flowering strips may indicate a conflict in landscape suitability regarding foraging for adult flower and larval prey resources. It seems that T. figulus is attracted to wildflower strips for adult feeding requirements (Fabian et al ., ), but that larval spider prey, although present, is less effectively caught in structurally diverse wildflower strips than simple arable fields (c.f. Rypstra et al ., ).…”
Section: Discussionmentioning
confidence: 99%